Dynamic Behavior of a SCARA Robot by using N-E Method for a Straight Line and Simulation of Motion by using Solidworks and Verification by Matlab/Simulink - Fernini Brahim; Mustapha Temmar (IAES International Journal of Robotics and Automation (IJRA), 2014)
SCARA (Selective Compliant Assembly Robot Arm) robot of serial architecture is widely used in assembly operations and operations "pick-place", it has been shown that use of robots improves the accuracy of assembly, and saves assembly time and cost as well. The most important condition for the choice of this kind of robot is the dynamic behavior for a given path, no closed solution for the dynamics of this important robot has been reported. This paper presents the study of the kinematics (forward and inverse) by using D-H notation and the dynamics of SCARA robot by using N-E methods. A computer code is developed for trajectory generation by using inverse kinematics, and calculates the variations of the torques of the links for a straight line (path rest to rest) between two positions for operation "pick-place". SCARA robot is constructed to achieve “pick-place» operation using SolidWorks software. And verification by Matlab/Simulink. The results of simulations were discussed. An agreement between the two softwares is certainly obtained herein